Polyphenol Profiles and Antioxidant Properties of Ethanol Extracts from Osmanthus Fragrans (Thunb.) Lour. Flowers - Li Hong-Ling; Chai Zhi; Shen Garry X.; Li Chun-Yang (Polish Journal of Food and Nutrition Sciences)
This study evaluated the antioxidant activity of ethanol extracts of Osmanthus fragrans (Thunb.) Lour. flowers (EOF) and identified phenolic compounds in EOF using liquid chromatography-mass spectrometry. Nine compounds, 3-O-caffeoylquinic acid, caffeic acid 4-O-glucoside, salidroside, 5-O-coumaroylquinic acid, 4-O-coumaroylquinic acid, acteoside, ligustroside, fucosterol and arjunolic acid were identified. To our knowledge, caffeic acid 4-O-glucoside, 5-O-coumaroylquinic acid and 4-O-coumaroylquinic acid have not been detected in EOF. In vitro antioxidant activity analysis demonstrated that EOF possessed strong DPPH and ABTS radicals scavenging activity with EC50 values at 0.26±0.06 mg/mL and 0.36±0.01 mg/mL, respectively, and reducing power with Ab0.5 value at 13.04±0.16 μg/mL. The value of oxygen radical absorbance capacity (ORAC) was 333.23±13.39 μmol Trolox/g. Antioxidant activity assay in human umbilical vein endothelial cells (HUVEC) showed that the activity of superoxide dismutase (SOD) was significantly improved and the reactive oxygen species (ROS) was removed effectively from cells when treated with EOF of 300~3000 μg/L.